Physics Teachers’ Knowledge of Quantum Theory and its Relationship to their Understanding of the Nature of Science - Al-Zoubi, Abdullah Salem (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to investigate the level of physics teachers’ knowledge of quantum theory and its relationship to their understanding of the nature of science. Methods: To achieve the study’s objective, a descriptive correlational method was used. The study sample consisted of 29 teachers who teach physics at the secondary level in schools in the city of As-Salt, selected through convenience sampling. The study instruments included a test to measure the teachers’ knowledge of quantum theory, consisting of 30 multiple-choice questions, and a test to assess their understanding of the nature of science, consisting of 20 multiple-choice questions. Results: The results showed that the level of knowledge of quantum theory among physics teachers was high, and their understanding of the nature of science was also high. Additionally, a strong positive correlation was found between their understanding of quantum theory and the nature of science. Conclusions: The study provided several recommendations, the most important of which is considering the understanding of the nature of science as a fundamental approach to teaching quantum theory. It also recommended leveraging the experiences of secondary school physics teachers, particularly those related to the content of the curricula they teach and the strategies and teaching methods they adopt, to develop curricula and prepare science teachers at all educational levels.